1995
DOI: 10.1016/1044-0305(94)00089-i
|View full text |Cite
|
Sign up to set email alerts
|

Formation and characterization of the sulfur-containing distonic radical anion, , in the gas phase, in the gas phase

Abstract: Formation and characterization of the sulfur-containing distonic radical anion,E.CH2-S-E-CHCN, in the gas phase Born, M.; Ingemann Jorgensen, S.; Nibbering, N.M.M. Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…A series of high kinetic energy (8 keV) collision-induced dissociation (CID) experiments were performed (see the Experimental Section) in order to determine the structure of the various ions. The ions formed by proton abstraction from methoxyacetonitrile eliminate only a methyl radical upon 8 keV collision-induced dissociation, as observed earlier in drift-cell ICR studies, , and a similar observation is reported for the related ions generated from thiomethoxyacetonitrile, as described in a previous report . The collision-induced charge-reversal (CR) spectrum of the carbanion of the methoxyacetonitrile is shown in Figure .…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…A series of high kinetic energy (8 keV) collision-induced dissociation (CID) experiments were performed (see the Experimental Section) in order to determine the structure of the various ions. The ions formed by proton abstraction from methoxyacetonitrile eliminate only a methyl radical upon 8 keV collision-induced dissociation, as observed earlier in drift-cell ICR studies, , and a similar observation is reported for the related ions generated from thiomethoxyacetonitrile, as described in a previous report . The collision-induced charge-reversal (CR) spectrum of the carbanion of the methoxyacetonitrile is shown in Figure .…”
Section: Resultssupporting
confidence: 84%
“…The generation of the ions given in eqs 4−7 upon charge reversal and also the other ionic species formed (see Figure ) are in line with the carbanion structure shown in eq 1. For the related ion from thiomethoxyacetonitrile, a similar conclusion has been reached previously also on the basis of CR experiments . The charge-reversal spectrum of the ions formed by methyl radical loss from the carbanion of methoxyacetonitrile is shown in Figure , while the spectrum for the related sulfur-containing species is shown in Figure .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Biradical ions (distonic radical ions) are of great interest because they are key intermediates in some reactions, they are biologically important, they can be used to study the reactivities of radicals in the gas phase using the charge as a detection tool in mass spectroscopy, , they have unique chemical properties , which are not seen in conventional radical ions, and they can be used to study the singlet−triplet energy gaps in the corresponding neutral biradicals. Although numerous distonic radical anions have been generated using various methods, , there are relatively few published studies of their chemical reactivity in the gas phase. , Most of the previously studied distonic radical anions were formed via oxygen radical anion (O •- ) abstraction of H 2 •+ from a neutral precursor. ,, The products from these reactions are often a mixture of isomersdistonic radical anions and conventional radical anionswith the same m/z that are not easily distinguishable by mass spectroscopy . Since the presence of isomeric ions makes chemical studies of distonic radical anions difficult, only a few have been studied successfully using this method (most notably, the distonic 1,4-radical anion of tetramethyleneethane 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In these species, the charged and radical or biradical moieties are formally separate, and when the charged site is chemically inert, reactions of the radical or biradical portion of the molecule can be observed. Free radical reactions of distonic radical cations and anions have been investigated by several groups. We reported the generation of distonic biradical anions in the gas phase and a characterization of their spin-state-dependent reactivity …”
mentioning
confidence: 99%